The Development Process of Democratic Values of High School Students in Banda Aceh City - Putra, Irwan; Maimun, Maimun; Pranika, Cindy Ayu (Jambura Journal Civic Education, 2024)
Understanding and applying democratic values is one part of overcoming intolerant and discriminatory attitudes among students. The proposed solutions include strengthening extracurricular programs, active learning in the classroom, student participation in decision-making, integration of moral values in the curriculum, and regular program evaluation. This research examines the process of fostering democratic values for students at school. This study is a case study with a qualitative approach to gain an in-depth understanding of the phenomenon. Data were collected through interviews with 16 Civics teachers and 16 students and then analyzed using data reduction, data display, and verification. The results showed that fostering democratic values was not only carried out through extracurricular activities or learning in the classroom. But it is also organized with a co-curricular activity approach integrated into the Pancasila Student Profile Strengthening Project (P5). This includes simulating elections, changing the Osis chairperson, and distributing roles in class, such as class leader. In addition, the process of fostering democratic values also involves extracurricular activities such as Paskibra, PASCAL, Scouts, sports (such as futsal), debates, theatre, the annual ‘Realistig' event, dance studio, Rohis, law ambassador forum, spiritual activities (tahfidz), PIK-R, and PMR.